Strategic issue selling from subsidiaries to headquarters - Santos, Renato de Souza (2021)
There is a broad debate in international business literature about the strategic action of subsidiaries of multinational corporations generating innovations in the organization. These companies are lower than the parent and face obstacles to success by proposing something to the headquarters. To understand this phenomenon, we use the issue selling theory to explain how this influence exerted by the subsidiary can generate success despite the discrepancy between them. This research is divided into three articles. First, we performed a systematic literature review on how issue selling studies have been conducted regarding the conceptual definition and operationalization of the phenomenon; as a result, it was possible to point out and extract the insight of the little use of issue selling in the parent-subsidiary relationship and the pointing out to centralization obstacles and cultural differences. In the second article, we test the impact of issue selling packaging and process on foreign MNC subsidiaries, moderated by the centralization exercised by the head office, using a sample of 342 international subsidiaries. The result showed that centralization could be circumvented by the subsidiary manager when using the issue selling strategy. In the third article, we examine whether the national culture modifies the attention paid by the headquarters to issue selling performed by the subsidiary; this article is divided into two parts. Part A, with the same sample as the second article, we model the moderation of aggregate cultural distance; and part B, using a larger sample of 533 subsidiaries, with 191 locations, where we modeled as moderation five cultural dimensions of the matrix manager relevant to the literature. The result of study A showed that cultural distance was significant, while the result of study B showed that individual cultural dimensions are not significant for the issue selling strategy. This research brings some contributions, first to the issue selling theory, showing the possibility of improving the fundamental theory with the inclusion of Attention-based view in the framework and showing theoretical paths to be explored in aligning the framework with the studied contexts. Second, we reinforce how the issue selling strategy proves relevant to understanding the headquarters-subsidiary relationship with practical articles. And we show that the controls exercised by the headquarters need to be improved. The subsidiary needs to observe the cultural difference between it and the headquarters when proposing something new.